Erbium-activated silica-zirconia planar waveguides prepared by sol-gel route - Goncalves, Rogeria R.; Messaddeq, Younes [UNESP]; Chiasera, Alessandro; Jestin, Yoann; Ferrari, Maurizio; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V. Sa, 2008)
Er(3+) doped (100-x)SiO(2)-xZrO(2) planar waveguides were prepared by the sol-gel route, with x ranging from 10 up to 30 mol%. Multilayer films doped with 0.3 mol% Er(3+) ions were deposited on fused quartz substrates by the dip-coating technique. The thickness and refractive index were measured by m-line spectroscopy at different wavelengths. The fabrication protocol was optimized in order to confine one propagating mode at 1.5 mu m. Photoluminescence in the near and visible region indicated a crystalline local environment for the Er(3+) ion. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: planar waveguides; sol-gel; zirconia; silica; erbium; optical properties; photoluminescence